2008
DOI: 10.1007/s00330-008-1121-8
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided biopsy in patients with suspected ovarian carcinoma: a safe and effective technique?

Abstract: In patients with suspected advanced ovarian carcinoma, a precise histological diagnosis is required before commencing neo-adjuvant chemotherapy. This study aims to determine the diagnostic accuracy and complication rate of percutaneous biopsies performed under ultrasound or computed tomography guidance. Between 2002 to 2007, 60 consecutive image-guided percutaneous biopsies were performed in patients with suspected ovarian cancer. The following variables were recorded: tissue biopsied, imaging technique, exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 22 publications
1
15
0
2
Order By: Relevance
“…Несмотря на это, чувствительность и специ-фичность результатов КТ в определении тех-нической возможности выполнения оптималь-ной циторедукции составляет лишь 69,2-79 и 71,4-75 % соответственно, в то время как для определения стадии заболевания чувствитель-ность составляет не более 50 % при специфич-ности 85-90 % [6,21]. Имеются публикации, в которых достоверность КТ в оценке резекта-бельности опухолевого процесса при заболе-вании на стадиях III-IV по FIGO оценивается в 63 %, в связи с чем авторы рекомендуют отка-заться от данной методики при решении вопро-са о возможности оперативного лечения таких пациенток [22].…”
unclassified
See 1 more Smart Citation
“…Несмотря на это, чувствительность и специ-фичность результатов КТ в определении тех-нической возможности выполнения оптималь-ной циторедукции составляет лишь 69,2-79 и 71,4-75 % соответственно, в то время как для определения стадии заболевания чувствитель-ность составляет не более 50 % при специфич-ности 85-90 % [6,21]. Имеются публикации, в которых достоверность КТ в оценке резекта-бельности опухолевого процесса при заболе-вании на стадиях III-IV по FIGO оценивается в 63 %, в связи с чем авторы рекомендуют отка-заться от данной методики при решении вопро-са о возможности оперативного лечения таких пациенток [22].…”
unclassified
“…Некоторые исследования показывают, что данная методика является безопасной и в боль-шинстве случаев обеспечивает получение доста-точного количества материала для проведения гистологического исследования, позволяющего подтвердить диагноз и подобрать оптимальный режим химиотерапии [21,27]. Таблица 2…”
unclassified
“…We and others have already demonstrated that image-guided biopsies can be obtained in patients with ovarian cancer (Spencer et al , 2006; Griffin et al , 2009; Swisher et al , 2017), whilst many early phase clinical trials now include translational research biopsies to investigate pharmacodynamic biomarkers. However, there is widespread variation in the reporting of outcomes of biopsy-driven studies (Freeman et al , 2013) and few data on the utility of these biopsies for complex genomic studies.…”
mentioning
confidence: 99%
“…Image-guided biopsy is not traditionally employed in the diagnosis of abdominal TB or ovarian cancer. Ultrasound-guided biopsy yields a 25% accuracy in the diagnosis of abdominal tuberculosis10 and 87% accuracy for ovarian cancer [29]. While biopsy poses the theoretical risk of seeding ovarian tumor cells, it is rarely observed [29,30].…”
Section: Discussionmentioning
confidence: 99%